HADIST PENCIPTAAN PEREMPUAN DARI TULANG RUSUK (Analisis-Kritis Terhadap Pandangan Feminis) - Agusman, Ryandi (UIN Sumatera Utara Medan, 2019)
AbstracThis paper will further reveal the hadith about the creation of women from ribs by displaying various related hadith texts, capturing their sanad, analyzing their death through the comments of authoritative scholars. This study is a response to the feminist assumption that the hadith is gender biased or